Benefits of the SiO2-supported nickel phosphide catalyst on ethylene oligomerization - Shin, Mi; Jeong, Hwiram; Park, Myung June; Suh, Young Woong (Applied Catalysis A: General, 2020)
Although homogeneous catalytic systems have been central in ethylene oligomerization, the SiO2-Al2O3-supported nickel phosphide (Ni2P) catalyst was recently examined to be capable of transforming ethylene into higher olefins. Herein, better catalytic performance in ethylene oligomerization is achieved with Ni2P/SiO2 than Ni2P/SiO2-Al2O3 and Ni2P/Al2O3. As a factor influencing ethylene oligomerization, the particle size of Ni2P is the smallest over Ni2P/SiO2 due to strong metal-support interaction. While the oligomer productivity is affected by the density of Brønsted acid site present in the supported Ni2P catalysts, Ni2P/SiO2 has a relatively high ratio of Brønsted to Lewis acid sites. Moreover, Ni2P/SiO2 is able to easily generate and transfer hydrogen species via the Brønsted acid P[sbnd]OH groups, which would affect formation of nickel hydride species that is important in oligomerizing ethylene. Therefore, the above features of Ni2P/SiO2 are beneficial for ethylene oligomerization into higher olefins.
Keywords: Acid site; Catalytic performance; Catalytic system; Ethylene oligomerizations; Lewis acid site; Nickel phosphide; Strong metal support interaction; Supported nickel; Brønsted acid sites; Ethylene oligomerization; Nickel phosphide; Supports